2‐Methylcitrate cycle: a well‐regulated controller of Bacillus sporulation. (28th December 2019) - Zheng, Cao; Yu, Zhaoqing; Du, Cuiying; Gong, Yujing; Yin, Wen; Li, Xinfeng; Li, Zhou; Römling, Ute; Chou, Shan‐Ho; He, Jin
Summary: Bacillus thuringiensis is the most widely used eco‐friendly biopesticide, containing two primary determinants of biocontrol, endospore and insecticidal crystal proteins (ICPs). The 2‐methylcitrate cycle is a widespread carbon metabolic pathway playing a crucial role in channelling propionyl‐CoA, but with poorly understood metabolic regulatory mechanisms. Here, we dissect the transcriptional regulation of the 2‐methylcitrate cycle operon prpCDB and report its unprecedented role in controlling the sporulation process of B. thuringiensis . We found that the transcriptional activity of the prp operon encoding the three critical enzymes PrpC, PrpD, and PrpB in the 2‐methylcitrate cycle was negatively regulated by the two global transcription factors CcpA and AbrB, while positively regulated by the LysR family regulator CcpC, which jointly account for the fact that the 2‐methylcitrate cycle is specifically and highly active in the stationary phase of growth. We also found that the prpD mutant accumulated 2‐methylcitrate, the intermediate metabolite of the 2‐methylcitrate cycle, which delayed and inhibited sporulation at the early stage. Thus, our results not only revealed sophisticated transcriptional regulatory mechanisms for the metabolic 2‐methylcitrate cycle but also identified 2‐methylcitrate as a novel regulator of sporulation in B. thuringiensis .